General decision assurance principles and procedures for strategic planning - De Reuck, J.; Schmidenberg, Olive; Klass, Desmond (Inderscience Enterprises Pty.Ltd, 2003)
This paper addresses two perceived inadequacies in traditional approaches to strategic planning the paucity of well-articulated theoretical assumptions underlying strategic planning procedures, and an insufficient emphasis on the importance to the quality of the final outcome, of robust, group decision management processes in which to embed the planning procedures. A set of principles and procedures to address these short-comings are proposed.